Managing information in the workplace : (McGraw-Hill Glencoe, 2003)
The Professional Communication Series 1e--Public Speaking, Interviewing, Technical Communications, Multimedia Presentation Skills, and MANAGING INFORMATION In The WORKPLACE are flexible modules that cover the important communication skills students will need for their careers. Each module consists of 192 pages presented in 10 chapters. Each includes the following features: Workplace Tips, Communication @ Work, self-assessment activities, chapter summaries, key terms, Ethics in Action, Technology Tips, Global Notes, Quotable Quips, and application exercises and checklists. Components of each module are Student Edition, Student Edition with CD-ROM, Instructor Resource Manual with CD-ROM (including ExamView Pro and PowerPoint), Distance Education through PageOut, and a Web site.